Why and When Cognitive Job Insecurity Relates to Affective Job Insecurity? a Three-Study Exploration of Negative Rumination and the Tendency to Negative Gossip - Lopez-Bohle, S (Routledge, 2020)
The job insecurity literature distinguishes between cognitive job insecurity and affective job insecurity where cognitive job insecurity reflects perceptions regarding the likelihood of total job loss or job features loss and affective job insecurity refers to emotional reactions to that potential loss. Indeed, affective job insecurity is demonstrated to be an affective reaction to cognitive job insecurity. However, the relationship between cognitive job insecurity and affective job insecurity may be neither direct nor unconditional. Drawing from cognitive appraisal theory, this research takes a nuanced approach to exploring the mediating role of negative work rumination and the moderating role of the tendency to negative gossip in the relationship between cognitive job insecurity and affective job insecurity. We examined our hypotheses using three time-lagged survey studies with employees recruited from the U.S. and China. These studies found that negative work rumination mediated the relation between cognitive job insecurity and affective job insecurity (Studies 1–3) and the tendency to negative gossip attenuated the positive relation between cognitive job insecurity and affective job insecurity (Studies 1 and 2). Thus, this research advances the job insecurity literature by identifying a mediator and a moderator in the process of how employees may experience job insecurity. © 2020 Informa UK Limited, trading as Taylor & Francis.